Decentralized wastewater system practices in developing countries: A systematic review. (December 2022) - Muzioreva, Happison; Gumbo, Trynos; Kavishe, Neema; Moyo, Thembani; Musonda, Innocent
Abstract: Decentralized wastewater systems (DWWSs) are an alternative to the ever-expanding sanitation problems in developing countries. This systematic review aims to identify the decentralized wastewater management system practices in developing countries. The PRISMA methodology and the archival research methods were used to identify papers published in the last 20 years through Scopus and Google Scholar. The results showed that about 45% of the studies conducted performance analyses of different types of decentralized wastewater systems, indicating a relatively average rate of practice and implementation of decentralization in various developing countries, even though there are constraints that hinder the adoption of the systems. Graphical abstract: Image 1 Highlights: Decentralized wastewater systems potentially offer sustainable alternatives to centralized systems.. Critical evaluation of the use of decentralized technologies in developing countries revealed widespread adoption. Constructed wetlands are the most common decentralized wastewater technologies in use. Adoption advantages include cheap implementation costs, easy operation and maintenance, and resource reclamation. However developing countries face social, institutional, and policy challenges in their attempt to adopt these systems.